2020
DOI: 10.3390/ma13020465
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Temperatures on the Impact Strength of Concrete Based on Recycled Aggregate Made of Heat-Resistant Cullet

Abstract: The article presents results obtained during testing of concrete based on CEM I 42.5R Portland cement, fine and coarse aggregate, glass, volatile ash, and superplastifier. The concrete mixture was modified using filler consisting of bromosilicate heat resistant cullet. Recycled aggregate was added to the batch. Samples for the need of testing were produced as (100 × 100 × 100) mm cubes. Before commencing proper tests, samples have been heated within the temperature range of 20–800 °C. Tests carried out during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…It can also be influenced by the construction of the contact zone between the binder and the aggregate, as well as the reaction of the aggregate used with the binder, which may affect the porosity of the silicate. Changes in the binder-aggregate contact zone have also been noticed in the work Powęzka and Szulej [32]. However, by considering the results of water absorption, it was found that the proportion of open pores increased considerably (Figure 8).…”
Section: Resultssupporting
confidence: 66%
“…It can also be influenced by the construction of the contact zone between the binder and the aggregate, as well as the reaction of the aggregate used with the binder, which may affect the porosity of the silicate. Changes in the binder-aggregate contact zone have also been noticed in the work Powęzka and Szulej [32]. However, by considering the results of water absorption, it was found that the proportion of open pores increased considerably (Figure 8).…”
Section: Resultssupporting
confidence: 66%
“…Each obtained tonne of glass cullet allows a saving 800 kg of sand, 250 kg of soda and 180 kg of limestone powder. This shows that the usage of glass from recycling contributes to a reduction in the volume of landfills and widely promotes the circular economy [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glass used for the production of concrete needs to undergo a special processing procedure [ 5 , 11 ]. The whole material may be recycled.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations